Empowering Women in Development: Insights from the Health, Education, and Employment Sectors in West Sulawesi, Indonesia - Riswana; Jeffriansyah DSA; Hamzar; Rhena J.; Ahmed Absi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study explores the roles of women in development in West Sulawesi Province, Indonesia, focusing on three key dimensions: health, education, and employment. The research was motivated by ongoing gender disparities observed between women and men in these areas. The novelty of this study lies in its use of the most recent time series data from 2019 to 2023, the application of member-checking for data validation, and its status as the first comprehensive and updated study addressing this topic in the context of West Sulawesi. Employing a descriptive-qualitative approach, the study analyzed five-year data sourced directly from the Central Bureau of Statistics of West Sulawesi Province, supplemented by relevant previous research. Data validation was conducted through member checking and prolonged observation techniques to ensure credibility. The collected data were grouped and analyzed, then presented through statistical charts supported by narrative explanations. The findings reveal that in the health domain—measured through life expectancy—women generally exhibited better health outcomes than men. However, in the realm of education, as reflected in indicators such as expected years of schooling and average years of schooling, women significantly lagged behind their male counterparts. This educational gap correlates with employment outcomes, where female labor force participation remained notably lower than that of men. These findings carry important implications for public awareness and policy formulation. They highlight the critical importance of addressing educational inequality and serve as a foundation for future research, as well as a call to action for government stakeholders to design more inclusive and gender-responsive development policies.